The effectiveness of negative pressure wound therapy compared to the traditional method in the treatment of diabetic foot - Bogucka, Julia; Brzyska, Anna; Bojarska, Małgorzata; Burda, Bartosz (Journal of Education, Health and Sport, 2023)
Introduction and objective: Diabetes is one of the most common metabolic diseases in the world. Diabetic foot ulcers, which are often the result of the disease, are undoubtedly a nursing challenge. Negative pressure wound therapy (NPWT) is a new therapeutic method supporting wound healing, which has been useful in patients with diabetic foot. The purpose of this study is to compare the effectiveness of negative pressure therapy in comparison to the standard method in the treatment of diabetic foot. Review methods: In February 2023, articles found in the Medline (Pubmed) and Google Scholar databases were selected by using the following keywords: negative pressure wound therapy; VAC therapy; traditional dressing; standard moist wound care; diabetic foot. Brief description of the state of knowledge: NPWT has been proven to be associated with reduced healing time and faster appearance of granulation tissue, which is a sign of wound healing. Patients using this method require fewer dressing changes and surgical cleanings. Negative pressure therapy reduces the time to rehospitalisation and the risk of amputation or resection of the diabetic foot. Summary: Negative pressure wound therapy is more effective in the treatment of diabetic foot ulcers than traditional therapy. Despite the costs associated with NPWT being higher, the method proves to be more profitable. It is important to remember about good therapy technique and proper selection of patients.